Partai Politik dan Pembangunan Daerah: Studi Dinamika Elektoral di Sumatera Barat Pasca Reformasi - Damara Pradipta, Frans Tory; Hidayat, Novendra (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2025)
This study examines the dynamics of electoral politics in West Sumatra from the 1998 Reform Era to the 2024 General Election, focusing on the interrelationship between party system configuration, voter behavior, and regional development trajectories. Employing a qualitative approach with extensive literature review, secondary data from the General Elections Commission (KPU), and academic as well as media sources, this research provides a longitudinal analysis of legislative seat allocation trends, party dominance, and strategic maneuvers by key political actors, notably the Prosperous Justice Party (PKS) as the dominant executive power. Findings reveal that West Sumatra’s political landscape is deeply shaped by Minangkabau culture, Islamic traditions, and a robust diaspora network. Since the 2014 election, the rise of nationalist parties such as Gerindra, Golkar, and NasDem has demonstrated a gradual shift in voter orientation from ideological affiliation to rational and programmatic considerations. Legislative fragmentation has enhanced accountability mechanisms but has simultaneously slowed policy consensus-building processes, particularly in infrastructure and economic development planning. These dynamics highlight that democracy in West Sumatra is a product of the interplay between religious values, local cultural norms, and national political modernization. This study contributes to the literature on local democracy in Indonesia by offering a framework that emphasizes the linkages between electoral competition and governance performance. It also recommends multi-stakeholder consensus-based governance strategies to strengthen regional development effectiveness. West Sumatra can serve as a model of “value-based politics,” integrating culture, religion, and modernization as social capital for advancing democracy and sustainable development.